The young, the restless, and the dead : interviews with Canadian filmmakers - Melnyk, George (Film + media studies, 2008)
The Young, the Restless, and the Dead captures the spirit of Canadian filmmakers through interviews with the most accomplished and dynamic of yesterday's, today's, and tomorrow's film greats. Funny, provocative, and enlightening, the filmmakers reflect on their careers and explore with the interviewers the issues that challenge them. This book features an interview with a late director (Jean-Claude Lauzon) whose work is recognized in the canon as outstanding; interviews with filmmakers who are accomplished in their fields and have to their credit a sizeable body of work (Blake Corbet, Andre.